Lability of heavy metal species in aquatic humic substances characterized by ion exchange with cellulose phosphate - Rocha, J. C.; Toscano, IAS; Burba, P. (Elsevier B.V., 1997)
Labile metal species in aquatic humic substances (HSs) were characterized by ion exchange on cellulose phosphate (CellPhos) by applying an optimized batch procedure. The HSs investigated were pre-extracted from humic-rich waters by ultrafiltration and a resin XAD 8 procedure. The HS-metal species studied were formed by complexation with Cd(II), Ni(II), Cu(II), Mn(II) and Pb(II) as a function of time and the ratio ions to HSs. The kinetics and reaction order of this exchange process were studied. At the beginning (<3 min), the labile metal fractions are separated relatively quickly. After 3 min, the separation of the metal ions proceeds with uniform half-lives of about 12-14 min, revealing rather slow first-order kinetics. The metal exchange between HSs and CellPhos exhibited the following order of metal lability with the studied HSs: Cu > Pb > Mn > Ni > Cd. The required metal determinations were carried out by atomic absorption spectrometry.
Keywords: aquatic humic substances; cellulose phosphate; heavy metal species; ion exchange; lability